Pesticide control, physical control, or biological control? How to manage forest pests and diseases more effectively - Bai, Yuntao; Wang, Lan; Yuan, Xiaolong (Frontiers in Ecology and Evolution, 2023)
The frequent occurrence of forest diseases and insect pests has a significant impact on forest ecosystem. The government needs to take measures to protect the forest ecosystem. The common management modes of forest pests and diseases include pesticide control, physical control and biological control. In the process of governance, governments need to consider not only cost-effectiveness, but also the impact on the ecosystem. In this article, the differential game model under these three modes is constructed, and the equilibrium results are compared and analyzed. Finally, the research conclusion is drawn that under the biological control mode, the income generated by the unit control quantity is inversely proportional to the balanced control quantity. However, under the pesticide control and physical control mode, the revenue generated by the unit control quantity is proportional to the balanced control quantity. At the same time, under the biological control mode, the unit governance cost is proportional to the balanced control quantity. Under the pesticide control and physical control mode, the unit control cost is inversely proportional to the balanced control quantity. Social forces tend to adopt pesticide control. The government prefers physical control.